Enhancing Economic Growth Through Labor, Unemployment, Poverty, and Zakat Collection in Bengkulu Province - Nonie Afrianty; Muthi' 'Adilah Bahril; Sekar Mayang (Integrated Journal of Business and Economics (IJBE), 2026)
This study aims to analyze the effect of labor force participation, unemployment, poverty, and zakat collection on economic growth in Bengkulu Province, Indonesia. Using a quantitative approach with associative analysis, the research employs time-series data from 2020 to 2024 obtained from the Central Bureau of Statistics (BPS) and the National Zakat Board (BAZNAS). The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results show that labor force participation has a positive and significant impact on economic growth, while poverty and zakat collection also significantly affect economic growth in a negative and positive direction, respectively. However, the effect of unemployment on economic growth was found to be negative but not statistically significant. The R-square value of 0.883 indicates that 88.3% of the variation in economic growth can be explained by the four variables in the model. These findings highlight the importance of workforce empowerment, poverty alleviation, and optimizing zakat distribution in supporting inclusive and sustainable economic development. Policymakers are encouraged to integrate Islamic fiscal instruments such as zakat into regional development strategies to enhance social equity and economic resilience.